Persepsi Guru Terhadap Penilaian Autentik Yang Telah Disempurnakan Dalam Permendikbud Nomor 23 Tahun 2016 Di Sd Muhammadiyah Program Khusus Kottabarat - Meilita Sari, Selvi; , Honest Ummi Kaltsum, S.S. M.Hum (2017)
The research aims to describe: 1) Teacher's perceptions toward authentic assessment that has been perfected in Permendikbud Nomor 23 tahun 2016 in SD Muhammadiyah Program Khusus Kottabarat, 2) Obstacles faced by teachers in implementing authentic assessment, 3) the solution used by teachers in overcoming the obstacles encountered. This research used a qualitative research with phenomenology research design. Informant in this research is the vice principal of curriculum, class guardian 5B and 6A. the data collection techniques used were interviews, observative, and documentation. Testing the validity of the data obtained using the triangulation of methods and source. The stages of data analysis in this research is data reduction, data presentation, and conclusion. The results of this research teachers assume authentic assessment is good in the sense that include assessment of attitudes, knowledge and skills however, teachers are always trying to understand and improve the ability to perform better authentic assessment. Teachers have problems in conducting assessments spiritual attitudes and skills for example, teachers have difficulty in the determining the value of the attitude. The solution used by teachers is by discussing with the team that talks about the obstacles faced by each teacher. Keywords: 2016, Permendikbud nomor 23 tahun authentic assessment, perception.